AQUASCAPE TRAINING IN IMPROVING THE ENTREPRENEURIAL SPIRIT OF THE COMMUNITY OF BEREUNUT VILLAGE, SEULIMEUM DISTRICT, ACEH BEASAR DISTRICT - Dedi Fazriansyah Putra; Sari Afriani; Adli Waliul Perdana; Ismarica; Siti Maulida; Suraiya Nazlia; Said Ali Akbar; Siska Mellisa; Muchlisin ZA; Muhammadar; Abdullah Abbas; Iko Imelda Arisa; Nurfadillah; Adrian Damora; Kavinta Melanie; Cut Nuzlia; Cut Dara Dewi; Ichsan Rusydi (Jurnal Pengabdian Bangsa, 2023)
Beureunut is one of the villages in Mukim Lampanah, Seulimeum ​​District, Aceh Besar Regency. This village is close to the coast and is flowed by a river which has become an eel breeding location. The potential of Beureunut Village can be an opportunity to develop the Aquascape business. The potential in the form of small fish that can be used as ornamental fish and freshwater plants that can be obtained from rivers requires innovation so that it can be further developed so that it has added value and high selling value. This service activity aims to provide knowledge and skills about Aquascape entrepreneurship to the Beurenut village community which can become economic potential in the future. This activity will be carried out in September 2022 using the methods of counseling, training and assistance in making Aquascape. The results obtained were that the participants were very active and enthusiastic in participating in this activity and the evaluation showed a change in knowledge of up to 90% compared to before participating in this training. Therefore, it is hoped that consistent assistance and supervision is needed so that this activity can be carried out independently and become a potential income for the community in the future.